Growth factors regulate phospholipid biosynthesis in human fibroblast-like synoviocytes obtained from osteoarthritic knees - Sluzalska, Katarzyna D.; Liebisch, Gerhard; Wilhelm, Jochen; Ishaque, Bernd; Hackstein, Holger; Schmitz, Gerd; Rickert, Markus; Steinmeyer, Juergen; Justus Liebig University Giessen (My University, 2017)
Elevated levels of growth factors and phospholipids (PLs) have been found in osteoarthritic synovial fluid (SF), although the metabolic regulation of PLs is currently unknown. This study aimed to determine the effects of growth factors on the biosynthesis of PLs by fibroblast-like synoviocytes (FLS) obtained from human osteoarthritic knee joints. Electrospray ionization tandem mass spectrometry was applied to analyse the newly synthesized PLs. In the presence of stable isotope-labelled PL precursors, cultured FLS were treated with either transforming growth factor-ß1 (TGF-ß1), bone morphogenetic protein (BMP)-2, BMP-4, BMP-7 or insulin-like growth factor-1 (IGF-1) alone or in combination with specific inhibitors of cell signalling pathways. TGF-ß1 and IGF-1 markedly stimulated the biosynthesis of phosphatidylcholine (PC) before sphingomyelin (SM) and lysophosphatidylcholine (LPC) species were stimulated. BMPs elaborated less pronounced effects. The BMPs tested have different potentials to induce the biosynthesis of phosphatidylethanolamine (PE) and PE-based plasmalogens. Our study shows for the first time that TGF-ß1 and IGF-1 substantially regulate the biosynthesis of PC, SM and LPC in human FLS. The functional consequences of elevated levels of PLs require additional study. The BMPs tested may be joint protective in that they upregulate PE-based plasmalogens that function as endogenous antioxidants against reactive oxygen species.
Keywords: ddc:610